A Model of School Social Well-Being for Elementary School Students: A Mixed-Methods Approach - Malmir, Azizollah; Moafimadani, Seyedeh Khadijeh; Pali, Samira (KMAN Counseling & Psychology Nexus, 2026)
This study aimed to develop and validate a comprehensive model of school social well-being for elementary school students. The study employed a sequential exploratory mixed-methods design. In the qualitative phase, thematic analysis was conducted based on research synthesis and semi-structured interviews with 15 academic experts and education practitioners, selected through purposive sampling until theoretical saturation was achieved. In the quantitative phase, a fuzzy Delphi method was used to screen and confirm the importance of the identified components and indicators. Subsequently, a researcher-developed questionnaire was administered to 375 elementary school principals and teachers selected through simple random sampling. Data were analyzed using confirmatory factor analysis, partial least squares structural equation modeling, and the Best–Worst Method for prioritization, with analyses performed in SPSS, SmartPLS, and LINGO software. Inferential results supported a five-dimensional model of school social well-being, including social relationships, school environment and atmosphere, individual factors and personal interactions, cultural and educational factors, and structural and managerial factors. All factor loadings exceeded the acceptable threshold and were statistically significant. The measurement and structural models demonstrated adequate reliability, convergent validity, and discriminant validity. Path analysis indicated that all five dimensions had significant positive effects on school social well-being. Model fit indices and predictive relevance measures confirmed a strong overall model fit. Prioritization results showed that social relationships had the highest relative importance, followed by school environment and atmosphere, individual factors and personal interactions, cultural and educational factors, and structural and managerial factors. The findings indicate that school social well-being among elementary students is a multidimensional construct shaped by relational, environmental, individual, cultural, and organizational factors.